SOSIALISASI RANCANGAN PROGRAM BANK SAMPAH DIGITAL - Herlitriwulandari; Ingga Dewi Permata Sari (PT. CASA CENDEKIA MEDIA, 2025)
This community service project aims to increase household waste management awareness through the implementation of a Digital Waste Bank program. The initiative was developed to address the growing issue of improper waste disposal and low public participation in environmental sustainability. The program integrated digital technology with community-based education to encourage waste sorting, recycling, and saving practices. Using a participatory action approach, the activity involved 30 household participants selected based on their active involvement in community waste management initiatives. Data were collected through observations, questionnaires, and interviews before and after the program. Quantitative analysis using descriptive statistics and paired sample t-tests showed significant improvements in participants’ waste management knowledge and behavior. Qualitative results revealed positive changes in household habits, with participants becoming more disciplined in waste sorting and recognizing the economic value of recyclable materials. Overall, the Digital Waste Bank program effectively enhanced environmental awareness, digital literacy, and community empowerment, contributing to the development of a sustainable and eco-friendly lifestyle.